Summary of the Key Technologies for Metric Range Extension of Electric Vehicles - , Salami A. Nasirudeen; , M. A. Aminu; , M. S. Haruna; , E. N. C. Okafor (Archives of Current Research International, 2019)
Electric vehicle is a sustainable development which is capable of transforming the transport sector. It is a sustainable alternative to internal combustion engine-based vehicle. Its technology is based on utilization of sustainable energy resources which are eco-friendly and replenishes in nature. Wide deployment of electric vehicle is expected to minimize the challenge of fossil fuel depletion and greenhouse emissions are expected to be reduced. However, despite all aforementioned advantages of the electric vehicle, its wide deployment faces some challenges including cost, size and range anxiety. Electric vehicles have limited range which is one of the major factors affecting its market penetration. Researchers highlighted several strategies/methods of extending its driving range. Thus, this work presents a review of different strategies proposed on range extension of the electric vehicle. The strengths and weaknesses of some of the proposed methods are also presented in this work.